#TITLE_ALTERNATIVE# - DWI CAHYANI (NIM 15304040), SAVITRI
Solid waste generation in Indonesia is increasing along with the nation's population boom. The waste contains high level of organic matters (70-80 %). So, it is possible to be treated with biological treatments, either aerobic or anaerobic. One of the potential biowaste treatment process is Mechanical Biological Treatment Process (MBT Process) which is a combination of mechanical process and biological treatment. Mechanical process includes sorting, grinding, biowaste and additional water blending process, and separation of liquid and solid fraction of biowaste. The purpose of the research were to understand the influence of mechanical process of biowaste to liquid fraction biowaste characteristics and to understand blending process variation and separation process that produced optimum COD:N:P ratio for biological treatment. The optimum COD:N:P are 100:5:1 for aerobic treatment and 250:5:1 for anaerobic treatment. The optimum COD:N:P ratio is significantly needed in biological treatment. This research was conducted in laboratory scale by using traditional market biowaste. It included variations of additional waters (tap water, river water, and tofu industrial wastewater), biowaste to additional water ratios (1:1, 1:2, and 1:3), and biowaste blending times (30 seconds, 45 seconds, and 60 seconds). The research showed that optimum biowaste blending time was 45 seconds. Tofu industrial wastewater as additional water resulted in the highest concentration of COD, TKN, and total phosphate. COD:N ratio in liquid fraction biowaste from additional water such as tap water, river water, and tofu waste water are 36,92-78,19, 38,01-80,3, and 25,28-65,87. There was not COD:P ratio that approached optimum condition for aerobic and anaerobic treatment. Application of Mechanical Biological Treatment (MBT) process for treating biowaste in Indonesia is needed further examination, since existing solid waste management in Indonesia, systems and regulations, are different from developed countries which already implement MBT.